Ivories from Room SW 37, Fort Shalmaneser. 1: Commentary and Catalogue. 2: Plates - Herrmann, Georgina (1986)
With contributions by Barbara Parker Mallowan, K. A. Kitchen, A. R. Millard, Myra Shackley, May Cassar.